Structural and luminescence properties BaI2 : Eu2+, Eu3+ powders and BaO – B2O3/BaI2 : Eu2+, Eu3+ glass-ceramics - Salamakha, Tatsiana A.; Tratsiak, Yauhen V.; Trusova, Ekaterina E. (Journal of the Belarusian State University. Chemistry, 2017)
An original method of BaI2 : Eu2+, Eu3+ powders synthesis has been developed in this work. The structural, morphological and spectral-luminescence properties of these powders has been researched. Low-melted glasses BaO – B2O3 and method of BaO – B2O3 / BaI2 : Eu2+, Eu3+ glass-ceramics formation based on this glasses have been proposed. This glass-ceramics may be promising for use as a transformer of the solar spectrum UV component in the blue and red region of the spectrum in passive supplementary plants lighting.
Keywords: europium luminescence; barium iodide; glass-ceramics